Temperature and performance evaluation of multiprocessors chips by optimal control method - Porya Soltani Hanafi Por; Abbas Ramazani; Mojtaba Hosseini Toodeshki (Bulletin of Electrical Engineering and Informatics, 2023)
Multi-core processors support all modern electronic devices nowadays. However, temperature and performance management are one of the most critical issues in the design of today’s microprocessors. In this paper, we propose a framework by using an optimal control method based on fan speed and frequency control of the multi-core processor. The goal is to optimize performance and at the same time avoid violating an expected temperature. Our proposed method uses a high-precision thermal and power model for multi-core processors. This method is validated on asymmetric ODROID-XU4 multi-core processor. The experimental results show the ability of the proposed method to achieve the adequate trade-off between performance and temperature control.